DISASTER MANAGEMENT ORGANIZATION COMMUNICATION MITIGATION (ACEH TAMIANG CASE STUDY) - Syafriadi Lubis; Hasan Sazali; Hasnun Jauhari Ritonga (SOSIOEDUKASI, 2026)
This study aims to analyze in-depth public perceptions and assessments of organizational communication mitigation in disaster management in Aceh Tamiang Regency, specifically regarding information clarity, speed of message delivery, inter-agency coordination, and the level of public trust in disaster information received. Furthermore, this study aims to identify and evaluate various communication media used in disaster mitigation, both conventional and information technology-based, and assess their effectiveness in improving preparedness, risk understanding, and community response to disasters. This study employed a case study approach, with documentation as the data collection technique. The researchers also employed domain analysis, and triangulation as a data validity check technique. The results indicate that the Regional Disaster Management Agency (BPBD) has implemented organizational communication mitigation in Aceh Tamiang Regency through the use of social media, specifically the Instagram account @bpbd_acehtamiang, as the primary channel for disseminating disaster information, from early warnings of extreme weather events and evacuation activities to post-tropical cyclone Sinyar data updates. However, the research findings also revealed significant limitations in the effectiveness of this communication mitigation, primarily due to the limited human resources of the BPBD, which are not commensurate with the population of Aceh Tamiang, weak cross-agency coordination, and the suboptimal use of other communication media such as TikTok and YouTube, which tend to be passive and ceremonial. Public perceptions indicated dissatisfaction with the speed of response and distribution of post-disaster aid, which was considered slow and fraught with image interests, as well as the lack of structural and non-structural mitigation efforts such as area-based early warning, environmental management, and forest rehabilitation. Overall, the results of this study confirm that the communication mitigation of the Aceh Tamiang BPBD organization has not been carried out in an integrated, sustainable, and community-oriented manner, thus requiring strengthening the communication system, increasing institutional capacity, and a more educational and participatory media strategy